Історична інформаційна система “Електронний музей” - Жежнич, П. І.; Пелещишин, А. М. (Видавництво Національного університету “Львівська політехніка”, 2020)
This paper describes an historical information System “Electronic muséum”. The System description is performed according to object temporal methods. It con- sists of conceptuai and logical System model, The last paragraph includes System implémentation aspects.
Keywords: 681.3